Achievable QoS in an interference - Capone, J.M.
In this work, the region of achievable quality-of-service (QoS) is precisely described for a system of real-time heterogeneous variable bit rate (VBR) sources competing for slots (packet transmission times) of a time division multiple access (TDMA) frame. The QoS for each application is defined in terms of a maximum tolerable packet-dropping probability. Packets may be dropped due to delay violations and channel induced errors. The region of achievable QoS is precisely described for an interference/resource limited network by considering the underlying TDMA-multiple access control (TDMA-MAC) structure and the physical channel. A simple QoS-sensitive error-control protocol that combats the effects of the wireless channel while satisfying the real-time requirements is proposed and its impact on the region of achievable QoS is evaluated. The results presented here clearly illustrate the negative impact of a poor channel and the positive impact of the employed error-control protocol on the achievable QoS. The region of achievable QoS vectors is central to the call admission problem, and in this work, it is used to identify a class of scheduling policies capable of delivering any achievable performance
Keywords: QoS-sensitive error-control protocol; TDMA frame; TDMA-MAC.; TDMA-multiple access control; Achievable QoS vectors; Call admission problem; Channel induced errors; Delay violations; Error-control protocol; Interference/resource limited shared wireless channel; Maximum tolerable packet-dropping probability; Packet transmission times; Performance; Physical channel; Quality of service; Real-time heterogeneous VBR sources; Scheduling policies; Time division multiple access; Variable bit rate; Wireless ATM systems; Wireless channel